Comparative Proteomics of Extended-Spectrum Cephalosporin-Resistant Neisseria gonorrhoeae Isolates Demonstrates Altered Protein Synthesis, Metabolism, Substance Transport, and Membrane Permeability - Diao, Nannan; Yan, Guoquan; Yang, Yang; Dong, Yuan; Wang, Ying; Gu, Weiming (Frontiers in Microbiology, 2020)
Neisseria gonorrhoeae isolates exhibit resistance to extended-spectrum cephalosporins (ESCs), the last remaining option for first-line empirical monotherapy. Here, we investigated the proteomic profiles of N. gonorrhoeae clinical isolates with ESC resistance to support exploration of the antimicrobial resistance mechanisms for N. gonorrhoeae. We used comparative iTRAQ quantitative proteomics to investigate differential protein expression of three ESC-resistant N. gonorrhoeae clinical isolates using N. gonorrhoeae ATCC49226 as a reference strain. The expression of 40 proteins was downregulated and expression of 56 proteins was upregulated in all three ESC-resistant N. gonorrhoeae isolates. Proteins with predicted function of translation, ribosomal structure and biogenesis, as well as components of the Type IV secretory systems, were significantly upregulated. Two differentially expressed proteins of ABC transporters were also reported by other teams in proteomics studies of N. gonorrhoeae isolates under antimicrobial stress conditions. Differentially expressed proteins are involved in energy production and metabolism of carbohydrates and amino acids. Our results indicated that amino acid and carbohydrate metabolism, cell membrane structure, interbacterial DNA transfer, and ribosome components play critical roles in mediating ESC-resistance in N. gonorrhoeae. These findings facilitate a better understanding of the mechanisms of ESC-resistance in N. gonorrhoeae and provide useful information for identifying novel targets in the development of antimicrobials against N. gonorrhoeae.